pHLuc, a Ratiometric Luminescent Reporter for in vivo Monitoring of Tumor Acidosis - Ong, Tiffany T.; Ang, Zhiwei; Verma, Riva; Koean, Ricky; Tam, John Kit Chung; Ding, Jeak Ling (Frontiers in Bioengineering and Biotechnology, 2020)
Even under normoxia, cancer cells exhibit increased glucose uptake and glycolysis, an occurrence known as the Warburg effect. This altered metabolism results in increased lactic acid production, leading to extracellular acidosis and contributing to metastasis and chemoresistance. Current pH imaging methods are invasive, costly, or require long acquisition times, and may not be suitable for high-throughput pre-clinical small animal studies. Here, we present a ratiometric pH-sensitive bioluminescence reporter called pHLuc for in vivo monitoring of tumor acidosis. pHLuc consists of a pH-sensitive GFP (superecliptic pHluorin or SEP), a pH-stable OFP (Antares), and Nanoluc luciferase. The resulting reporter produces a pH-responsive green 510nm emission (from SEP) and a pH-insensitive red-orange 580nm emission (from Antares). The ratiometric readout (R580/510) is indicative of changes in extracellular pH (pHe). In vivo proof-of-concept experiments with NSG mice model bearing human synovial sarcoma SW982 xenografts that stably express the pHLuc reporter suggest that the level of acidosis varies across the tumor. Altogether, we demonstrate the diagnostic value of pHLuc as a bioluminescent reporter for pH variations across the tumor microenvironment. The pHLuc reporter plasmids constructed in this work are available from Addgene.